'The Swarm Principle': A Sub-National Spatial Analysis of Aid Targeting and Donor Coordination in Sub-Saharan Africa. Issue 1 (15th May 2020) - Marineau, Josiah F.; Findley, Michael G.
Do bilateral and multilateral foreign aid donors target poverty? To answer that question, we present a framework for assessing the quality of aid targeting sub-nationally. If donors cluster aid in areas with concentrated poverty, or spread out aid in areas of diffuse poverty, then we conclude that donors are targeting aid well. Furthermore, because co-financing may be a mechanism that improves coordination and information-sharing among donors, we examine whether the frequency of donor co-financing increases the quality of aid targeting. Recently released sub-national georeferenced foreign aid data for all bilateral and multilateral donors are available in five sub-Saharan African countries, making it possible to map the placement of foreign aid along with sub-national poverty levels. Results indicate that foreign donors target poverty in some countries but not others, and higher co-financing is associated with lower quality targeting across all cases.